Both Free Indole-3-Acetic Acid and Photosynthetic Performance are Important Players in the Response of Medicago truncatula to Urea and Ammonium Nutrition Under Axenic Conditions - Esteban, Raquel; Royo, Beatriz; Urarte, Estibaliz; Zamarreño, Ángel M.; Garcia-Mina, José M.; Moran, Jose F. (Frontiers in Plant Science, 2016)
We aimed to identify the early stress response and plant performance of Medicago truncatula growing in axenic medium with ammonium or urea as the sole source of nitrogen with respect to nitrate based nutrition through biomass measurements, auxin contents analyses, root system architecture response analyses, and physiological determinations. Both ammonium and ureic nutrition severely affected the root system architecture, resulting in changes in the main elongation rate, lateral root development and insert position from the base. The auxin content decreased in both urea- and ammonium- treated roots; however, only the ammonium- treated plants were affected at the shoot level. The analysis of chlorophyll a fluorescence transients showed that ammonium affected photosystem II, but urea did not impair photosynthetic activity. Superoxide dismutase isoenzymes in the plastids were moderately affected by urea and ammonium in the roots. Overall, our results showed that low N doses from different sources had no remarkable effects on M. truncatula, with the exception of the differential phenotypic root response. High dose of both ammonium and urea caused great changes at plant length, auxin content and physiological determinations. The interesting correlations found between the shoot auxin pool, the plant length, and the parameter “performance index”, obtained from the chlorophyll a fluorescence rise kinetics measurements, indicated that both IAA pool and performance index are an important part of the response of M. truncatula under ammonium or urea as a sole N source.